Metabolic parameters of rats prone to display wild-running of the audiogenic crisis and fighting induced by REM-sleep deprivation - Moraes, Gabriel Parmezani [UNESP]; Rafacho, Alex [UNESP]; Bosqueiro, José Roberto [UNESP]; Hoshino, Katsumasa [UNESP]; Paula, Hugo Medeiros Garrido [UNESP] (My University, 2010)
Total sleep or selective REM-sleep deprivation (SD) increases aggressiveness. Rats that display fighting when submitted to sleep-deprivation are those that manifest wild running (WR), a panic-like flight that precedes tonic-clonic seizures induced by intense acoustic stimulation (audiogenic epilepsy). The incidence of WR-sensitive rats in the colonies around the world may reach 20%, which makes important to know the other characteristics of these animals for both sleep and other kinds of experimental research. Based on the report of their reduced body weight, we investigated some glucose metabolism parameters. Methods: Adult male Wistar rats were submitted to high-intensity acoustic stimulation (112dB, 60s) and then classified as WR-sensitive or WR-resistant rats. Glycemia and insulinemia, measured by glucometer and radioimmunoassay, respectively, and body weight were analyzed during three months. At the end of this period, intraperitoneal glucose and insulin tolerance tests were performed, and hepatic fat and glycogen content were also determined. Results: WR-sensitive rats showed proportionally less gain of body mass compared to the resistant ones (p<0.05) in initial measurements, but this tendency did not sustain thereafter. Interestingly, fasting glycemia was significantly lower in the WR-sensitive group throughout the experiment, compared to WR-resistant rats. No significant differences between groups were found in insulinemia, peripheral glucose and insulin tolerance, and hepatic glycogen. However, WR-sensitive rats increased hepatic fat content significantly after a 12-hour fasting. Conclusions: Slow weight gain, decreased fasting glycemia and hepatic steatosis suggest a possible accelerated energetic metabolism or low resistance to food deprivation, which could partially explain the reduced body weight of WR-sensitive rats.

A privação total ou seletiva de sono REM aumenta a agressividade. Ratos que manifestam brigas quando submetidos a tal priva- ção são os mesmos que manifestam a corrida selvagem (WR, wild running), uma fuga panicoforme que precede a convulsão tônico-clônica induzida pela estimulação sonora intensa (epilepsia audiogênica). A incidência de ratos sensíveis à WR nas colônias ao redor do mundo pode alcançar 20%, e isso torna importante conhecer as outras características desses animais tanto nos estudos de sono como em outras espécies de investigação experimental. Baseados no relato de que esses animais têm peso corporal reduzido, foram investigados alguns parâ- metros do metabolismo da glicose. Métodos: Ratos Wistar machos adultos foram submetidos à estimulação acústica de alta intensidade (112 dB, 60s) e classificados como propensos ou resistentes à WR. A glicemia e insulinemia foram medidas por glicosímetro e por radioimunoensaio, respectivamente. O peso corporal foi avaliado por mais de três meses. Ao final do período, os testes de tolerância à glicose e à insulina administrada intraperitonealmente foram efetivados paralelamente às determinações do conteúdo hepático de gorduras e de glicogênio. Resultados: Os ratos propensos à WR mostraram ganhar relativamente menos massa corporal em relação aos animais resistentes (p<0,05) no início das observações; entretanto, esta tendência não se manteve subsequentemente. De maneira interessante, a glicemia em jejum foi significativamente menor no grupo de animais propensos à WR quando comparados aos animais resistentes. Não foram encontradas diferenças significativas entre os grupos no tocante à insulinemia, tolerância à glicose e à insulina administrada perifericamente, assim como no glicogênio hepático. Contudo, os ratos propensos à WR aumentaram significantemente o conteúdo de gordura hepática após 12 horas de jejum. Conclusões: O ganho lento de peso, a redução das glicemias de jejum e a esteatose hepática sugerem a possibilidade de um metabolismo energético acelerado ou baixa resistência à privação alimentar, o que pode explicar parcialmente o peso corporal reduzido em ratos propensos à WR.
Keywords: Running; Sleep deprivation/physiopathology; Sleep deprivation/metabolism; Acoustic stimulation; Aggression; Panic/physiology; Blood glucose/metabolism; Adipose tissue/metabolism; Privação do sono/fisiopatologia; Privação do sono/metabolismo; Estimulação acústica; Agressão; Pânico/fisiologia; Glicemia/metabolismo; Tecido adiposo/metabolismo; Peso corporal; Convulsões/metabolismo; Epilepsia reflexa/fisiopatologia